"Experimentation and modeling for the apparent elongation viscosity of polymer melts with the White–Metzner model". (30th September 2014) - Lin, Gwo‐Geng; Chang, Jin‐Ton; Kuo, Ting‐Wei
<x xml:space="preserve">Abstract</x> The measurement of the apparent elongation viscosity (ηe) of several polyolefin melts was conducted in this study by using the isothermal fiber‐spinning method. The White–Metzner (W–M) model was used to analyze the spinning flow of the polymer melts and, thus, the elongation viscosity was predicted at elongation strain rates ranging from 0 to approximately 5 s−1. The values of the model parameters required in the W–M model were obtained by curve fitting the experimental data obtained from the shear measurements. The elongation viscosity predicted using the W–M model was in good agreement with the experimental results of fiber spinning. In addition, ηe could also be estimated directly from the measured shear viscosity (ηS) with a formulation using the W–M model; the subsequently obtained elongation viscosity and Trouton ratio (TR) were reasonable within a wide range of strain rates. Based on the experimental and theoretical results, the polyolefin with a high molecular weight was observed to have high elongation viscosity, and the polymer with a broad molecular weight distribution also possessed high ηe. The TR value of the commercial polypropylene (PP‐1040) began to increase from 3 at a deformation rate of 0.1 s−1 and grew up asymptotically to 10, whereas the TR of high‐density polyethylene (HDPE‐606) remained nearly at 3 within the entire range of strain rates. Copyright © 2014 John Wiley & Sons, Ltd.